Kontribusi Imam al-Nawawi Dalam Pengembangan Madhhab Shafi'i - Luthfi Hadi Aminuddin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2011)
In the history of Shafi'i’s madhhab, the figure of Imam al-Nawa wi has a very significant role. The results of his ijtihad is always used as a Shafi`iyah scholar reference, even when the scholars differed in opinions, then his idea regarded as